Распознавание и поиск изображений логотипов на основе инвариантных признаков - Марченко, Е. Н. (ХНУРЕ, 2011)
This work is devoted to the recognition and search of images by the moment invariants. Within the research the conclusion about the suitability of application of the moment invariants for binary image recognition was made. The results of the researches were used in the logotype search system for identification of similar templates.
Keywords: инвариантный признак; логотип